FACTORS INFLUENCING CUSTOMERSâ TIPPING BEHAVIOUR IN RESTAURANTS IN LUZERN - Jessica, Jessica (Jurnal Hospitality dan Manajemen Jasa, 2015)
Food and food service that are widely known today have always played an important role in Europe. Cultural differences, also high quality and variety of meals provided in Europe have become the main reason why there are so many restaurants as they are now, including in Luzern. Thus, resulting in a culture of dining out, which cannot be separated from the norm of tipping. Since the 18th century, tipping has become a custom in Europe. People give tips to express their gratitude for the service provided, and some give tips simply because it is expected to do so. However, previous studies from hospitality academicians and researchers stated that there are many other factors behind tipping phenomenon. Regarding this matter, this study was conducted to review customersâ tipping motivations and further investigate factors influencing customersâ tipping behaviour, specifically in table service restaurants in Luzern. Both primary and secondary researches were used in this study. Primary research was conducted through quantitative research by implementing survey strategy using questionnaire, which resulting in 80 usable responses. The results shows that people tip based on product quality and service received. Secondary research was also conducted by reviewing books, journals, magazine and newspaper articles, and webpages.